Getting stable: an evaluation of the incentives for permanent contracts in Italy - Emanuele Ciani; Guido De Blasio (IZA Journal of European Labor Studies, 2015)
There is little evidence as to the effectiveness of incentives for the conversion of fixed-term contracts into permanent jobs. We aim at filling this gap by studying a recent Italian program which provides benefits for employers who convert contracts for workers in specific demographic groups (females, younger men). Due to funding constraints, the incentives were available only for a few days, allowing us to employ a difference-in-differences strategy between similar short periods. Using administrative microdata for the Veneto region, we show that the subsidy increased conversions by 83% on average, with no substitution effects over time or across groups of workers.
Keywords: J21; J41; J48; 330; Fixed-term contracts; Permanent employment; Diff-in-diffs